Leadership Influence To Organizational Culture: Implication to Quality Information System - Rapina Rapina; Yenni Carolina; Johannes Buntoro Darmasetiawan; Libertus Baene (People and Behavior Analysis, 2025)
The dynamic nature of today's business climate has heightened the role of leadership in shaping a dynamic company culture. Effective leadership gives clear direction and strategic alignment, allowing information systems to thrive while supporting company goals. The purpose of this research is to investigate the links between leadership, organizational culture, and the quality of accounting information systems (AIS). A quantitative research design was adopted, with data collected from 67 individuals selected through stratified random sampling from various sections of the organization.  Data was gathered using a structured questionnaire, and the effect of organizational culture and leadership on AIS quality was evaluated using Structural Equation Modeling – Partial Least Squares (SEM-PLS). The results highlight how important leadership is in creating an organizational culture that supports the mission and objectives of the business. Employee perceptions of accounting procedures are positively impacted by this alignment, which raises the caliber of AIS and increases corporate competitiveness. This study is interesting since it focuses on how leadership shapes organizational culture and directly enhances AIS quality, providing insightful information for companies aiming for efficiency and long-term growth.